Uniportal video‐assisted thoracic surgery approach for simultaneous lung cancer and thymic carcinoma: Case report and literature review. Issue 3 (21st December 2021) - Frasca, Luca; Tacchi, Giovanni; Longo, Filippo; Marziali, Valentina; De Peppo, Valerio; Moscardelli, Alessandro; Crucitti, Pierfilippo
Abstract: Thymic carcinoma is an epithelial tumor derived from thymic epithelial cells. Thymic tumors may be associated with other simultaneous and/or metachronous extra‐thymic tumors (e.g., lung cancer). Here, we report a case of simultaneous surgical management of lung and mediastinal neoplasm together with a review of the literature. During radiological follow‐up for prostate and colorectal cancer, an 82‐year‐old man was diagnosed with lung cancer with simultaneous mediastinal suspected neoplasm. Both were surgically removed with a single intervention performed via a uniportal video‐assisted thoracic surgery (uni‐VATS) approach. The literature emphasizes how extra‐thymic cancer can be diagnosed before, concurrently and consecutively with thymic neoplasia. The surgical treatment of such simultaneous cancer is challenging. We succeeded in the excision of both neoplasia with a mini‐invasive surgical technique. This report highlights the feasibility of uniportal VATS in a patient with very unusual clinical and oncological history. Abstract : A uniportal video‐assisted thoracoscopic approach allows to deal with challenging clinical and oncological situations (concurrent thyimic squamous cell carcinoma and lung adenocarcinoma). Multidisciplinary evaluation should be carried out in elderly patients.